Fabrication and Characterization of Bacteria Cellulose, Polyvinyl Alcohol and Fragrant Oil With Antimicrobial Effect For Wound Healing Application - Mohd Syazwan, Safie (2013)
The experiment is about the production of the wound healing product from the combination of three types of materials that is bacteria cellulose, polyvinyl alcohol (PVA) and also essential oil. The objective of the experiment is to fabricate the bacteria cellulose, polyvinyl alcohol (PVA) and essential oil with antibacterial properties for wound healing application. The method of the process can be divides into three that is preparation of bacterial cellulose, the fabrication of bacterial cellulose with PVA and essential oil and lastly characterization the product produced. In the fabrication process, the bacterial cellulose will be added with 1:4, 1:2, 3:4, and 1:1 ratios of PVA to BC. Acetobactor Xylinum is the bacteria that had been use to produce the bacteria cellulose. Among the method that will be used to characterize the product are Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), gas pycnometer, water absorption test and also antibacterial effect test. The entire tests are to make sure that the biocomposite film has the characteristics need as the wound healing material. The final product is in the form of film that is suitable to be used as the wound healing application. The result for the experiment is the higher ratios of PVA to BC content in the mixture of bacterial cellulose and essential oil will show the highest amount of the bond in the film. So, the present of the high amount of molecular bond inside the film will make it stronger. Then, for the SEM test, the higher ratios of PVA to BC content in the film will give the smooth morphology, homogenous and compact structure to the film. For moisture absorption test, the higher ratios of PVA to BC content will make the film can absorb more moisture compared to less amount of PVA content. For bacteria test, the higher ratios of PVA to BC content is more effective to kill more bacteria and lastly for the density test, the higher ratios of PVA to BC content in the film will give the higher density to the film. As the recommendation, use gram positive bacteria for the next study to see the effect of the biocomposite film with different ratio of PVA to BC content to the gram positive bacteria. Beside, try to produce the fragrant oil by yourself t to make sure the purity of the oil and also use the combination of several fragrant oil to know the effectiveness of it antimicrobial effect.